2004
DOI: 10.1038/modpathol.3800179
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus-6-associated acute lymphadenitis in immunocompetent adults

Abstract: In contrast to other causes of herpetic lymphadenitis, the histological features associated with human herpesvirus-6 (HHV-6) infection have remained elusive since its discovery in 1986. We describe the histologic and phenotypic changes associated with acute HHV-6 lymphadenitis in two immunocompetent adults who presented with fever, fatigue, generalized lymphadenopathy, and elevated liver enzymes. Serologic tests for human immunodeficiency virus, acute Epstein-Barr virus, and cytomegalovirus infection were nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
(23 reference statements)
0
28
1
Order By: Relevance
“…[38][39][40] In adults, HHV-6 infection may present with a mononucleosislike syndrome with acute lymphadenitis. 41 Disseminated infection may be associated with hepatitis, pneumonia, marrow suppression, and encephalitis. HHV-6 has also been detected, albeit at low levels, in Hodgkin's lymphoma and angioimmunoblastic lymphadenopathy, 42 and has been implicated in multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] In adults, HHV-6 infection may present with a mononucleosislike syndrome with acute lymphadenitis. 41 Disseminated infection may be associated with hepatitis, pneumonia, marrow suppression, and encephalitis. HHV-6 has also been detected, albeit at low levels, in Hodgkin's lymphoma and angioimmunoblastic lymphadenopathy, 42 and has been implicated in multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Virus infection has a significant effect on EC physiology, upregulating the production of specific chemokines, such as MCP-1, IL-8, and RANTES (14,15). The observations that lymph nodes are a site of viral persistence and viral infection has been associated to lymphadenitis (16) suggest that lymphatic ECs (LECs) from lymphatic tissue might be even more relevant for HHV-6 biology than vascular ECs. However, no information is available on the ability of HHV-6 to infect LECs, due to the lack of suitable in vitro systems.…”
mentioning
confidence: 99%
“…A previous study demonstrated the presence of HHV-6-infected cells in the lymph node in a case of DRESS syndrome [14]. Another group also reported a patient with HHV-6-associated lymphadenopathy who had taken medication including sulfasalazine before admission and had died because of multiple organ failure (Case 2 of the reference [13]). These two cases are similar to the present case of a DRESS syndrome with HHV-6-associated lymphadenitis.…”
Section: Discussionmentioning
confidence: 86%
“…Although lymphadenopathy is very common among the patients with DRESS syndrome, so far there have been a few immunohistochemical studies of the lymphadenopathy [13,14]. A previous study demonstrated the presence of HHV-6-infected cells in the lymph node in a case of DRESS syndrome [14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation